2015
DOI: 10.1177/1060028015593093
|View full text |Cite
|
Sign up to set email alerts
|

Dual Angiotensin Receptor and Neprilysin Inhibition with Sacubitril/Valsartan in Chronic Systolic Heart Failure

Abstract: Sacubitril/valsartan significantly improved morbidity and mortality in patients with chronic HFrEF but will require careful application to "real-world" populations of HFrEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 66 publications
(146 reference statements)
0
23
0
Order By: Relevance
“…It is a potent vasopeptidase inhibitor for both neprilysin and ACE [1]. Dose titration trials showed increase in natriuretic peptides and decrease in ACE activity.…”
Section: Neprilysin: the Latest Piece In The Neurohormonal Puzzlementioning
confidence: 98%
See 2 more Smart Citations
“…It is a potent vasopeptidase inhibitor for both neprilysin and ACE [1]. Dose titration trials showed increase in natriuretic peptides and decrease in ACE activity.…”
Section: Neprilysin: the Latest Piece In The Neurohormonal Puzzlementioning
confidence: 98%
“…CNP is found mostly in the kidney, central nervous system, and vasculature and released in response to cytokines and endothelium-dependent agonists [3]. Natriuretic peptides can also be stimulated by angiotensin II and endothelium-1 [1].…”
Section: Focus On Neurohormonal Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…58,59 The most challenging part is to reciprocate these results in general population in clinical practice.…”
Section: Challenges Of Paradigm-hf Trial In Clinical Practicementioning
confidence: 99%
“…Valsartan acts on the angiotensin-aldosterone system, thereby reducing vasoconstriction, sodium and water retention and ventricular remodelling 2,8,10. The active metabolite of sacubitril inhibits the enzyme neprilysin, an endopeptidase that degrades vasoactive natriuretic peptides, bradykinin and angiotensin II, leading to an increased concentration of the endogenous natriuretic peptides with enhancement of diuresis, natriuresis and vasodilation.…”
Section: What Is Sacubitril Valsartan?mentioning
confidence: 99%